2021
DOI: 10.3892/etm.2021.9767
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑22 contributes to dexamethasone‑induced osteoblast differentiation inhibition and dysfunction through targeting caveolin‑3 expression in osteoblastic cells

Abstract: Osteoporosis is a common complication of long-term use of glucocorticoids (GCs) characterized by the loss of bone mass and damage of the microarchitecture as well as osteoblast dysfunction. Previous studies have demonstrated that microRNA-22 (miR-22) is the negative modulator of osteogenesis that may target caveolin-3 (CAV3), which has been reported to enhance bone formation and inhibit the progression of osteoporosis as well as apoptosis. The present study aimed to investigate whether miR-22 may be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As Cav3 mRNA was consistantly down-regulated with aging in the male myocardium (to a lesser degree in females), we hypothesized whether this transcriptional repression could be related to microRNA regulation of gene expression as seen by others with cardiac aging and disease (Boon et al, 2013; Gatsiou et al, 2021; Bei et al, 2018). In-silico bioinformatic analysis of Cav3 and literature search (Chen et al, 2015; Li et al, 2021; Zhang et al, 2018) for Cav3 -related microRNAs revealed miR-22 & miR-101b as top candidates for regulation of Cav3 . Although miR-22 and miR-101b showed significant age-dependant changes in the normoxic heart, their expression pattern did not (inversely) correlate with Cav3 transcriptional changes seen in the normoxic and post-ischemic male hearts.…”
Section: Discussionmentioning
confidence: 99%
“…As Cav3 mRNA was consistantly down-regulated with aging in the male myocardium (to a lesser degree in females), we hypothesized whether this transcriptional repression could be related to microRNA regulation of gene expression as seen by others with cardiac aging and disease (Boon et al, 2013; Gatsiou et al, 2021; Bei et al, 2018). In-silico bioinformatic analysis of Cav3 and literature search (Chen et al, 2015; Li et al, 2021; Zhang et al, 2018) for Cav3 -related microRNAs revealed miR-22 & miR-101b as top candidates for regulation of Cav3 . Although miR-22 and miR-101b showed significant age-dependant changes in the normoxic heart, their expression pattern did not (inversely) correlate with Cav3 transcriptional changes seen in the normoxic and post-ischemic male hearts.…”
Section: Discussionmentioning
confidence: 99%